2018
DOI: 10.1093/hmg/ddy371
|View full text |Cite
|
Sign up to set email alerts
|

A recurrent missense variant inSLC9A7causes nonsyndromic X-linked intellectual disability with alteration of Golgi acidification and aberrant glycosylation

Abstract: We report two unrelated families with multigenerational nonsyndromic intellectual disability (ID) segregating with a recurrent de novo missense variant (c.1543C>T:p.Leu515Phe) in the alkali cation/proton exchanger gene SLC9A7 (also commonly referred to as NHE7). SLC9A7 is located on human X chromosome at Xp11.3 and has not yet been associated with a human phenotype. The gene is widely transcribed, but especially abundant in brain, skeletal muscle and various secretory tissues. Within cells, SLC9A7 resides in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 128 publications
1
19
0
Order By: Relevance
“…Khayat et al (2019) recently described a new pH homeostasis-associated disease with multigenerational non-syndromic intellectual disability (ID). The disease is caused by missense mutations in the alkali cation/proton exchanger NHE7 (SLC9A7).…”
Section: Altered Golgi Homeostasis In Golgi Dysfunction and Diseasementioning
confidence: 99%
“…Khayat et al (2019) recently described a new pH homeostasis-associated disease with multigenerational non-syndromic intellectual disability (ID). The disease is caused by missense mutations in the alkali cation/proton exchanger NHE7 (SLC9A7).…”
Section: Altered Golgi Homeostasis In Golgi Dysfunction and Diseasementioning
confidence: 99%
“…Two other recent clinical studies investigating two unrelated ion transport mutations are relevant to our hypothesis, as they have been linked to changes in Golgi pH and glycosylation. Khayat et al reported a multigenerational nonsyndromic intellectual disability that is the result of mutation in the alkali cation/proton exchanger gene SLC9A7 (also commonly referred to as NHE7) located on human X chromosome [9]. The gene is widely transcribed in various secretory tissues with prominent enrichment in the trans-Golgi network and post-Golgi vesicles.…”
Section: The Gs and Bs Phenotypic Overlappingmentioning
confidence: 99%
“…The last XLID update published, estimated that 141 genes are associated with XLID. Since then, more genes have been associated to XLID such as CXorf56 , HS6ST2 , NAA15 , POLA1 and SLC9A7 (Figure ). However, the link of some of these genes to XLID is still questionable .…”
Section: Introductionmentioning
confidence: 99%